Differential role of PVP on the synthesis of plasmonic gold nanostructures and their catalytic and SERS properties1. Issue 83 (25th August 2016) - Verma, Manoj; Kedia, Abhitosh; Newmai, M. Boazbou; Kumar, P. Senthil
Abstract : Differential role of PVP modified with halide ions has been meticulously studied for in situ tuning of Au nanoparticle growth utilizing XRD measurements together with FTIR data, thus quantifying their catalysis and SERS applications. Abstract : We have systematically utilized the simple yet uncommon XRD measurements together with FTIR data for not only quantifying the phase purity of as-synthesized Au nanoparticles, but also for meticulously interpreting the differential role of PVP in conjunction with its halide modified counterpart in the in situ fine-tuning of the nanoparticle growth. We thereby illustrate the robustness of the present synthetic protocol, further substantiating our relentless quest in achieving size/shape tunable metal nanostructures with high precision/yield by solely utilizing the full potential of the versatile polymer, polyvinyl pyrrolidone (PVP). Sincere efforts were undertaken in corroborating the optical plasmonic signatures of the different as-prepared Au nanostructures with the corresponding TEM measurements. Further, the comparative catalytic (4-nitroaniline to para -phenylenediamine) as well as surface enhanced raman scattering (of crystal violet dye molecules) investigations distinctly demonstrate a constructive structure–property correlation among the different Au nanostructures stabilized by the same polymer, the varied surface conformations of which solely dictate the physico-chemical properties in an illustrious manner, thereby establishing a new paradigm for better quantification of complex metal nanoarchitectures in general.